2019
DOI: 10.1186/s12969-019-0331-8
|View full text |Cite
|
Sign up to set email alerts
|

A delayed diagnosis of eosinophilic granulomatosis with polyangiitis complicated with extensive artery occlusion of lower extremities in children: case report and literature review

Abstract: Background Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare systemic vasculitis in children. A delayed or missed diagnosis of pediatric EGPA is common, owing to the atypical clinical manifestation and limited recognition of this disorder. The vasculitis in EGPA typically involves small to medium size vessels. Extensive occlusion of arteries in the extremities was being extremely rare and has never been reported in children. Case presentation A 10-year and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The prevalence and incidence of HES is unknown, but it is considered a rare disease in children and affected adults between 20 and 50 years old, with a 9:1 male-female ratio [12] and EGPA is a rare systemic vasculitis in children [16]. Statistical data and scientific publications show that HES and EGPA are exceedingly rare.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and incidence of HES is unknown, but it is considered a rare disease in children and affected adults between 20 and 50 years old, with a 9:1 male-female ratio [12] and EGPA is a rare systemic vasculitis in children [16]. Statistical data and scientific publications show that HES and EGPA are exceedingly rare.…”
Section: Discussionmentioning
confidence: 99%
“…EGPA is a type of ANCA-associated vasculitis that predominantly affects small-and medium-sized vessels of many organs simultaneously [6]. Most common manifestations in children are seen in the respiratory tract (69%), cutaneous tissue (61-62%), gastrointestinal tract (46%), cardiovascular system (46%), paranasal sinus abnormality (38%), arthritis/arthralgia (38%), and peripheral nerves (15%) [7][8][9][10][11]. In adults, other respiratory features also come to observation while the overall pattern of involvement is almost similar to children.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that cutaneous manifestations are present in 40% to 81% of EGPA patients (16). It has been reported that the most common presenting features of EGPA in children are: pulmonary (69%), skin (61-64%), gastrointestinal (46%), and cardiac manifestations (46%); paranasal sinus abnormality (38%); arthritis/arthralgia (38%); neurological involvement (15%); and even vasculitis (15,(17)(18)(19). In another study of children, the respiratory system was found to be mostly involved, mainly the upper airways (85%), while other frequently involved organ systems were the skin (71%), digestive tract (64%), and heart (57%) (20).…”
Section: Discussionmentioning
confidence: 99%